Effect of Upright Position on Pain and Duration of the Active Phase of the First Stage of Labor among Women in Labor in the Work Area of Tasikmalaya TPMB - Melsa Sagita Imaniar; Tatu Septiani Nurhikmah; Sherly Laksmining; Sandrina Rahmatul (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
Prolonged labor is one of causes of maternal and infant death. Several causes of prolonged labor are inefficient uterine contractions, presentation or position of the fetus, inadequate pelvic bones or abnormalities of maternal soft tissues, which result in failure to progress in labor and an increase in the incidence of Caesarean section delivery. The upright position will encourage stronger and more efficient contractions, wherein gravity will occur to keep the baby's head pressed towards the lower uterine segment so as to help cervical dilation and shorten the duration of labor. Upright positions in the first stage of labor include walking, standing, sitting, half-sitting, kneeling, and crawling positions. This study aims to determine the effect of upright position compared to supine position on the level of pain and the duration of the active phase of the first stage of labor among primigravida women in labor. This was a quasi-experimental study with a post-test only design. There were 100 study samples who were assigned in the control group and the intervention group, consisting of 50 respondents, respectively. The study was conducted at the Tasikmalaya TPMB. Data collection was carried out for approximately 6 months on March-August 2022. The results showed that primigravida women in the active phase of the first stage of labor with upright position had a shorter duration of labor compared to those with supine position. Independent t test results obtained a p value equals 0.000 (p is less than 0.05). Such finding indicated a statistically significant difference. Based on the results of the data analysis, it can be concluded that there was a significant difference in the duration of the active phase of the first stage of labor between upright position and supine position among women in labor in the Work Area of Tasikmalaya TPMB.